Development of a collagen dual-species biofilm model.The behaviour of P. aeruginosa and S. aureus during planktonic and biofilm mode of growth - Temur, Özlem (My University, 2020)
The prevalence of chronic wounds is increasing every year with aging population and with chronic diseases such as diabetes and obesity. Chronic wounds do not only affect many people worldwide but also brings major costs to the healthcare systems globally. The wounds are colonised by both planktonic (free-living) bacteria and bacteria in biofilms. Two species of bacteria, namely P. aeruginosa and S. aureus are commonly found in chronic wounds and can result in severe infections together. Although chronic wounds and wounds in general are polymicrobial, i.e. colonised by several species, in vitro test methods are still single-species. In this thesis work, there was an attempt to develop a dual-species collagen biofilm model with P. aeruginosa and S. aureus. The goal was to develop a model in which P. aeruginosa and S. aureus stayed at the same concentrations at 48 hours when both species had reached the stationary phase. The growth behaviour of P. aeruginosa and S. aureus in planktonic mono- and dual-species cultures with and without agitation was determined and compared to the results acquired from mono- and dual-species experiments in biofilms. It was found that the concentration of S. aureus decreased in dual-species experiments at 48 hours. The reduction in concentration could be linked to the presence of virulence factors produced by P. aeruginosa. The start inoculum concentration of P. aeruginosa was adjusted to lower values to investigate if S. aureus managed to survive in environments with lower concentration of P. aeruginosa. However, regardless of the start inoculum concentration of P. aeruginosa, a reduction of S. aureus could be seen at 48 hours. In conclusion, the development of the dual-species collagen model was not fulfilled as S. aureus did not manage to survive at same concentrations at 48 hours as when it reached the stationary phase. However, pre-established biofilms of S. aureus resulted in the smallest reduction and could possibly be optimised further.
Keywords: chronic wounds; biofilm; collagen; dual-species; bacteria; Pseudomonas aeruginosa; Staphylococcus aureus; in vitro model; planktonic; test method